Occupancy estimation and modeling inferring patterns and dynamics of species occurrence - MacKenzie, Darryl I.; Royle, J. Andrew; Bailey, Larissa L.; Nichols, James D.; Pollock, Kenneth H.; Hines, James E. (London Academic Press, 2017)
Occupancy Estimation and Modeling: Inferring Patterns and Dynamics of Species Occurrence, Second Edition, provides a synthesis of model-based approaches for analyzing presence-absence data, allowing for imperfect detection. Beginning from the relatively simple case of estimating the proportion of area or sampling units occupied at the time of surveying, the authors describe a wide variety of extensions that have been developed since the early 2000s. This provides an improved insight about species and community ecology, including, detection heterogeneity; correlated detections; spatial autocorrelation; multiple states or classes of occupancy; changes in occupancy over time; species co-occurrence; community-level modeling, and more. Occupancy Estimation and Modeling: Inferring Patterns and Dynamics of Species Occurrence, Second Edition has been greatly expanded and detail is provided regarding the estimation methods and examples of their application are given. Important study design recommendations are also covered to give a well rounded view of modeling.--Provided by publisher.
Part I. background and concepts -- 1. Introduction -- 2. Occupancy applications -- 3. Fundamental principles of statistical inference -- Part II. Single-species, single-season occupancy models -- 4. Basic presence/absence situation -- 5. Beyond two occupancy states -- 6. Extensions to basic approaches -- 7. Modeling heterogeneous detection probabilities -- Part III. Single-species, multiple-season occupancy -- 8. Basic presence/absence situation -- 9. More than two occupancy states -- 10. Further topics -- Part IV. Study design -- 11. Design of single-season occupancy studies -- 12. Multiple-season study design -- Part V. Advanced topics -- 13. Integrated modeling of habitat and occupancy dynamics -- 14. Species co-occurrence -- 15. Occupancy in community-level studies -- 16. Final comments.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Animal populations -- Estimates; Animal populations -- Mathematical models; Electronic books